Pecan agroforestry systems improve soil quality by stimulating enzyme activity - Wang, Zhaocheng; Zhou, Mengyu; Liu, Hua; Huang, Cheng; Ma, Yuhua; Ge, Hao xin; Ge, Xiang; Fu, Songling (PeerJ, 2022)
Background Forest and plantation intercropping are efficient agroforestry systems that optimize land use and promote agroforestry around the world. However, diverse agroforestry systems on the same upper-plantation differently affect the physical and chemical properties of the soil. Methods The treatments for this study included a single cultivation (CK) pecan control and three agroforestry systems (pecan + Paeonia suffruticosa + Hemerocallis citrina, pecan + Paeonia suffruticosa, and pecan + Paeonia lactiflora). Soil samples were categorized according to the sampling depth (0–20 cm, 20–40 cm, 40–60 cm). Results The results demonstrated that the bulk density (BD) of soil under the pecan agroforestry system (PPH and PPL) was reduced by 16.13% and 7.10%, respectively, and the soil moisture content (MC) and total soil porosity (TPO) increased. Improvements in the physical properties of the soil under the PPS agroforestry system were not obvious when compared with the pecan monoculture. The soil total phosphorus (TP), total nitrogen (TN), available potassium (AK), and total carbon (TC) increased significantly, while the soil urease (S-UE), alkaline phosphatase (S-AKP), and 1,4-β-N-acetylglucosamines (S-NAG) enzyme activity also increased significantly, following agroforestry. Overall, the pecan agroforestry system significantly improved the physical properties of the pecan plantation soil, enriched the soil nutrients, and increased the activity of soil enzymes related to TC, TN, and TP cycles.
Keywords: Pecan; Agroforestry; Soil nutrients; Enzyme activity